Safety and Efficacy of Postoperative Indwelling Popliteal Nerve Catheters for Outpatient Charcot-Marie-Tooth Surgery. (April 2022) - An, Tonya; Schwartz, Elliot; Kissen, Michael; Pollock, Gabriel; Pfeffer, Glenn
Background: Outpatient surgical deformity correction for Charcot-Marie-Tooth (CMT) disease is limited by effective postoperative pain control. Our previous institutional protocol for foot and ankle surgery in this population included preoperative single-injection nerve blocks, but patients often experienced uncontrolled pain when the block wore off postoperative day 0 or 1, resulting in high opioid requirements and unplanned emergency department visits. The use of ultrasonography-guided continuous nerve catheters in CMT patients has not previously been studied. We aimed to prospectively investigate the safety and efficacy of ultrasonography-guided indwelling popliteal catheters in CMT patients undergoing outpatient foot deformity correction surgery. Methods: Twenty CMT patients, average 28 (range 13-53) years old, undergoing reconstructive surgery by a single foot and ankle attending surgeon were consented for preoperative ultrasonography-guided popliteal catheters. This series included 24 total outpatient procedures; 4 were staged bilateral. Indwelling popliteal catheters were maintained on discharge, providing continuous infusion until postoperative day (POD) 3, and then self-discontinued. Patients were prescribed oxycodone 5 mg (60-80 pills) as needed for breakthrough pain. Outcomes collected included daily pain scores (0-10), an opioid pill count on POD 14, and patient satisfaction ratings. Neurologic evaluation by 5-point 10g Semmes-Weinstein monofilament testing was performed preoperatively and on POD 14. Results: There were no observed catheter-site infections or hematomas. Nine of the patients had pre-existing sensory deficits involving at least 2 areas on the 5-point monofilament test. Postoperative testing showed these deficits were unchanged and there were no instances of new sensory deficits. Postoperative pain scores were typically low, with median values (interquartile ranges [IQRs]) of 3.5 (2.0-5.0) on POD 1, 2.5 (2.0-5.0) on POD 2, and 2.5 (1.0-3.75) on POD 3. At POD 14, pain was 1.0 (0-1.0). Patients consumed a median of 25 oxycodone pills (IQR 8-43) over 2 weeks, less than half the prescribed number. Patient satisfaction was high. All patients reported they would choose to have a nerve catheter again for a similar surgery. Conclusion: This cases series demonstrated that regional anesthesia using ultrasonography-guided indwelling popliteal catheters was safe and effective for pain control in CMT patients undergoing outpatient foot and ankle surgery. Opioid consumption was comparable to published rates following major bony procedures, and no patients required emergent treatment or hospital admission for uncontrolled pain. No new sensory deficits were detected and patients with underlying sensory deficits remained unchanged. Patients were highly satisfied. Level of Evidence: Level IV, case series.